Exploring consumers' attitude towards cultured meat in Italy. (April 2019) - Mancini, Maria Cecilia; Antonioli, Federico
Abstract: Cultured meat may be a novel food that would overcome the limits of conventional meat production. This paper assesses the willingness to try, buy and pay for cultured meat among a sample of Italian consumers, unveiling the attitudes towards an engineered food on the part of a consumer oriented in favour of the Mediterranean diet. A survey was conducted by submitting a questionnaire to 525 Italian consumers. Consumers showed higher agreement with the statements concerning positive externalities than the intrinsic characteristics of cultured meat, and more than half of the respondents (54%) stated that they would be willing to try cultured meat. The profile for a potential consumer of cultured meat was young, highly educated, somewhat familiar with cultured meat, a meat consumer and willing to reduce meat consumption. However, the survey findings may be biased by the unavailability of the product on the market and the information provided to the respondents focused on the potential benefits of cultured meat. Highlights: Participants' perception is more positive towards extrinsic than intrinsic attributes of cultured meat. Consumers need to be reassured on the product's quality and taste of cultured meat. Positive perception is not necessarily predictive of the potential willingness to pay for cultured meat. Meat consumers rather than vegetarians/vegans seem to be willing to pay for cultured meat.